A Cluster Randomized Controlled Trial on the Effectiveness of the Building Educators’ Skills in Adolescent Mental Health (BEAM) Program for Improving Secondary School Educators’ Confidence, Behavior, Knowledge, and Attitudes Toward Student Mental Health - O’Dea, Bridianne; Parker, Belinda; Batterham, Philip J.; Chakouch, Cassandra; Mackinnon, Andrew J.; Whitton, Alexis E.; Newby, Jill M.; Subotic-Kerry, Mirjana; Gayed, Aimee; Harvey, Samuel B. (Journal of Teacher Education, 2023)
Secondary school educators are well placed to recognize and respond to mental illness in adolescents; however, many report low confidence and skills in doing so. A confirmatory cluster randomized controlled trial involving 295 educators (Mean age: 40.10 years, SD: 10.47; 76.6% female, 2.7% Aboriginal or Torres Strait Islander) from 73 Australian secondary schools (22 in rural-regional locations) evaluated the effectiveness of a new professional development training program that aimed to improve secondary school educators’ confidence, behavior, knowledge, and attitudes toward student mental health. Relative to the control, training participants reported significantly greater levels of confidence in recognizing and responding to student mental health issues, perceived mental health knowledge and mental health awareness, and mental health literacy, at post-intervention (10-weeks post-baseline; d = 0.26–0.35) and at 3-month follow-up (d = −0.21 to 0.41). Findings indicate that the Building Educators’ skills in Adolescent Mental health (BEAM) program improves important training outcomes for educators in the domain of student mental health.